The Influence of Servant Leadership and Organizational Culture through Employee Integrity on the Performance of Civil Servants at the Office of Education, Youth and Sports (DISDIKPORA) of Bali Province - Wilantari, Sang Ayu Ketut Sidan; Sumada, I Made; Kartika, I Made (Jurnal Ilmiah Global Education, 2025)
The performance of civil servants at the Bali Provincial Department of Education, Youth, and Sports (Disdikpora) has not been optimal, as reflected in the decline of several performance indicators in the 2022–2023 Government Performance Accountability Report (LAKIP). This study aims to analyze the influence of servant leadership and organizational culture on the performance of civil servants through employee integrity as a mediating variable. The research employs a quantitative approach with a descriptive-explanatory method. Data were collected through questionnaires distributed to 104 civil servants at the Bali Provincial Disdikpora. Data analysis utilized Structural Equation Modeling (SEM) with Partial Least Squares (PLS) using SmartPLS 3.0 software. The results indicate that servant leadership and organizational culture significantly and positively influence civil servant performance directly and indirectly through employee integrity. Employee integrity also significantly and positively affects performance. The study recommends that the Bali Provincial Disdikpora implement servant leadership and strengthen an organizational culture that supports employee integrity to enhance performance.